Maternal First Trimester TSH Concentrations: Do They Affect Perinatal and Endocrine Outcomes? - Fraenkel, M.; Shafat, T.; Erez, O.; Lichtenstein, Y.; Awesat, J.; Novack, V.; Tsur, A. (Hormone and Metabolic Research, 2016)
We aimed to examine the distribution of 1st trimester TSH and evaluate its association with perinatal outcomes and future development of maternal thyrotoxicosis. This retrospective cohort study included data of all women without prior thyroid disease who delivered a singleton at our medical center from 1/2001 to 12/2011 and had a 1st trimester TSH<4.0 mU/l. Women were divided according to 1st trimester TSH concentrations into quartiles and by predefined TSH values (mU/l): 1) TSH<0.1; 2) TSH 0.11–0.2; 3) TSH 0.21–0.4; and 4) TSH 0.4–4. Obstetrical outcomes, hCG concentrations, and future thyroid status were collected from electronic medical records. A total of 13 841 women fulfilled the inclusion criteria. Mean maternal TSH concentration at 5 weeks of gestation was 2.09±0.83 mU/l and decreased to 1.29±0.87 mU/l in weeks 8–9 with an increase towards the end of the 1st trimester. Odds ratio for future thyrotoxicosis was 3.64 in the lowest compared to the highest TSH quartile and 10.03 in those with TSH<0.1 compared to TSH 0.41–4 mU/l. Rates of female fetuses were higher in the low TSH quartiles and in the lower TSH groups, however baby gender was not associated with increased risk of future thyrotoxicosis. Low maternal 1st trimester TSH quartiles or concentrations were not associated with adverse pregnancy outcome. Only a minor fraction of pregnant women with a low first tirmester TSH subsequently developed future thyrotoxicosis.
Keywords: pregnancy; thyroid function; thyrotoxicosis; pregnancy outcomes